Effect of the height of the observation line on the the diffraction curve in GPR prospecting. Issue 3 (1st August 2014) - Persico, Raffaele; Leucci, Giovanni; Matera, Loredana; de Giorgi, Lara; Soldovieri, Francesco; Cataldo, Andrea; Cannazza, Giuseppe; De Benedetto, Egidio
ABSTRACT: This paper deals with the shape of the GPR diffraction curve in dependence of the distance of the measurement line from to the air/soil interface. It will be shown that the diffraction curve changes with respect to the case of data gathered at the air‐soil interface, and the calculation of the diffraction curve requires the solution of a fourth degree algebraic equation. The solution in closed form of this equation will be presented, and a physical discussion of the effects of the non‐null height of the observation line will be provided.